Novel source/drain contact structure for a-IGZO devices: Oxygen-scavenger-layer metal-interlayer-semiconductor (OSL MIS) approach - Sungjoo Song; Jong-Hyun Kim; Jongyoun Park; Seung-Hwan Kim; Dongjin Ko; Hyejung Choi; Seiyon Kim; Hyun-Yong Yu (Applied Surface Science Advances)
The engineering of Schottky barrier height (SBH) at source/drain (S/D) contacts is a crucial technology in the next generation nanoelectronics. Recently, amorphous indium gallium zinc oxide (a-IGZO) has gained prominence for its application to stackable 3-dimensional (3D) dynamic random-access memory (DRAM) due to its ultra-low off-current and low-temperature fabrication. However, a high contact resistance of a-IGZO still limits the device performance. Despite various attempts to address the high contact resistance issue, including the metal-interlayer-semiconductor (MIS) contact structure, a novel approach is needed. Here, we propose an oxygen-scavenger-layer MIS (OSL MIS) contact structure which employs oxygen areal density (OAD) modulated OSL as the interlayer. The OSL MIS has been shown to improve the contact resistance through three key effects. 1) The interlayer doping effect, 2) a diffusion of oxygen ions from a-IGZO to interlayer, generates shallow donors in a-IGZO, and 3) the movement of oxygen ion induces the interface dipole. With these effects, the effective SBH and a contact resistivity were reduced to 0.119 eV and 1.36E-5 Ω·cm2, respectively. The proposed OSL MIS contact structure of a-IGZO using OAD modulation technique, shows enormous potential in improving the performance of amorphous oxide semiconductor based advanced electronic devices.